Competencies of Nurses in Crisis Response: A Recent Study - Glezzeelyne Pascual Pascua (New Horizons in Medicine and Medical Research Vol. 11, 2022)
Clinical decision making and assessment skills are salient elements of rapid response afferent limb. Hence, clinical competence along with the ability of the nurse to recognize signs of clinical deterioration, interpret gathered assessment data to arrive with sound clinical judgement promptly is considered cornerstone to activate RRT (rapid response team) and attain positive patient outcome. This study aimed to identify competence of nurses in crisis response in terms of conducting clinical assessment and decision-making model used by nurses in activating the RRT; determine the factors that affect the nurses’ decision to activate RRT; determine the reason of referrals in different areas/ units and prevalence of RRT activation as compared to code blue; determine the impact of RRT; and design or enhance current RRT protocol. Both quantitative and qualitative method is utilized. The data generated in this study suggest that senior nurses have showed confidence and ability to detect signs of clinical deterioration that empower them to activate RRT when needed. Whereas, junior nurses usually confirm clinical assessments with senior nurses before deciding to activate RRT and intervening. Nurses in the study used both intuitive and analytical decision-making model. Nurses’ clinical acumen, emotional responses, and impact and influence of RRT are the identified themes. Knowledge of the criteria is considered as one of the triggers to act and activate RRT. Albeit clear institutional guidelines and well-defined criteria abridge process of decision making and determine immediate action; hence, increases positive patient outcome. Enhanced RRT pathway combines patient relative participation, incorporation of MEWS in the activation criteria, and curtailing the pathway of reaching the responsible physician.